A potential biomarker of cognitive impairment: The olfactory dysfunction and its genes expression. Issue 12 (27th October 2022) - Song, Jiayi; Xu, Jiahui; Yuan, Wei; Li, Ruixue; Guo, Hui; Gao, Hanshu; Gu, Cuiying; Feng, Wenjing; Ma, Yanan; Guo, Haiqiang; Sun, Zhaoqing; Zheng, Liqiang
Abstract: Objective: Accumulation evidence has reported that olfactory impairment may be an essential clinical marker and predictor of mild cognitive impairment or Alzheimer's disease. Method: Participants were enrolled in the population‐based, prospective study in Fuxin county, Liaoning province, China between 2019 and 2021. An inverse probability weighting logistic regression and mixed‐effect models were performed to explore the association between dysosmia and cognition and rate of change in cognition, respectively. Besides, we utilized the Robust Rank Aggregation method to integrated three eligible datasets from the Gene Expression Omnibus to identify differential expressed genes. Results: A total of 4695 participants were enrolled and 4221 of those were eligible for our cross‐sectional study. The mean (SD) age was 59.93(9.78) years, 64.8% were men. Over a 2‐year follow‐up, of the 2088 participants who completed follow‐up, 1559 participants were eligible for our longitude cohort study. We observed an association between dysosmia and an increased risk of cognitive impairment (OR, 0.47, [95% CI, 0.35–0.64]; p < 0.001). The OR (95% CI) for cognition in females with dysosmia was higher than (OR, 0.73[0.51, 1.05], p = .007) that for males with dysosmia (OR, 0.25[0.15, 0.42], p < 0.001; P for interaction <0.001). Dysosmia was also associated with more rapid decline in calculation ability ( p < 0.001). Besides, several DEGs were identified, which are mainly associated with olfactory transduction, detection of chemical stimulus involved in sensory perception of smell, sensory perception of smell, olfactory receptor activity and odorant binding. Interpretation: These findings proved novel insight into identifying olfactory dysfunction as potential biomarker for diagnosis of cognitive impairment.